How do the attitudes, confidence, knowledge and understanding differ in pre-registration healthcare students towards treating people with chronic pain: an observational, cross-sectional study. (3rd September 2021) - Carroll, Sean Paul; Augeard, Nathan; Tennant, Jacob; Seenan, Christopher
Abstract: Background: Attitudes, knowledge and understanding (K&U) may predispose practitioner adherence to clinical guidelines for chronic pain. To date, there are no data exploring this in adult, mental health and paediatric nursing, or occupational therapy, podiatry and physiotherapy student healthcare professionals at the same institution. Methods: We approached 1383 students enrolled on pre-registration healthcare programmes at a Scottish University, using the Health Care Providers' Pain and Impairment Relationship Scale (HC-PAIRS) and Pain Understanding and Confidence Questionnaire (PUnCQ). Results: Three hundred and forty-six students completed the survey (response rate 25%). There was a significant effect of degree discipline on HC-PAIRS and PUnCQ with a moderate effect size of η p 2 = .212 and η p 2 = .204, respectively. Postgraduate pre-registration physiotherapy students had more positive attitudes towards function with pain, M (SD) HC-PAIRS score = 49.6(8.9), 95%CI = 46.5–52.8, and greater confidence towards management of chronic pain M (SD) = 6.3, 95%CI = 5.9–6.8 compared to the other disciplines surveyed. Undergraduate physiotherapy and mental health nursing also displayed significantly more positive attitudes M (SD) = 55.2 (10.2), 95%CI 53.3–57.2 and 62.6 (7.6), 60.1–65.2, respectively. Conclusions: Physiotherapy students have more biopsychosocial-orientated attitudes, and higher confidence towards the management of people in pain than the other disciplines surveyed despite similar levels of K&U of pain.